Mud volcanoes and dissolution structures as kinematic markers during salt tectonic deformation. (20th September 2021) - Kirkham, Chris; Cartwright, Joe
Abstract: The recognition of linear trails of fluid escape pipes that have been deformed by salt flow have recently been suggested to offer a novel approach to reconstructing the internal kinematics of thick salt sequences deforming under gravity. These deformed pipes constrain a number of key parameters for salt tectonic analysis including the salt flow direction, translation distance of the top salt and overburden, the internal flow profile and from the flow velocity, the bulk viscosity of the salt. Here we interpret and characterise two previously unrecognised large‐scale strain markers within a salt sequence that may be equally as valuable as the deformed pipes for constraining salt flow. This study is based on the interpretation of a ca. 4, 600 km 2 3D seismic survey from the outer slope of the Nile Cone, offshore Egypt, located at the boundary between the extensional and translational domains of the deformed marginal region of the Messinian salt basin. We mapped five deformed pipe trails that allow us to constrain the average flow velocity of the top salt, at ca. 2 mm/yr over the past 2–3 Myrs. The salt flowed in a basinward NW/NNW direction away from the basin margin. In addition, we mapped two large (ca. 2 km diameter) salt dissolution depressions formed by subjacent dissolution of the evaporites. These are presently located down the salt flow direction of a large remnant erosional high at the base of the salt, and in the general alignment of one of the pipe trails. We therefore argue that this dissolution structure most likely formed by fluid venting from the base salt high, and as such can be used to measure translation direction, distance and average velocity. The second of the two novel kinematic indicators requires mapping of genetically connected mud volcanoes and their depletion zones. The study area contains over 400 individual mud volcanoes that are sourced from beneath the salt and erupted from the Early Pliocene to Recent. A subset of these, extruded at or near to the present day seafloor, have well imaged pre‐salt depletion zones vertically beneath the erupted volcanic cones. A smaller subset, typically buried Early Pliocene extrusions, is found to have volcanic cones that are systematically offset laterally from their corresponding depletion zones, with an offset direction and distances closely matched with other kinematic markers. Hence we suggest that mud volcanic plumbing systems can provide another independent kinematic marker from which to infer salt flow regime. Abstract : Mud volcano plumbing systems and dissolution structures present novel kinematic markers during salt tectonic deformation. The offset of their genetically connected pre‐salt and post‐salt components records the translation direction, distance, average velocity and allows the salt flow regime to be inferred. The widespread distribution of these kinematic markers in the Western Nile provides calibration of salt flow over an area > 3000 km 2 . Mud volcano systems and dissolution structures can be added to deformed fluid escape pipes, salt‐detached ramp syncline basins and deformed intra‐salt structures as part of a growing suite of kinematic markers for reconstructing salt flow.